Assignment of Patients to Hospitals in a Case of a Large-Scale Earthquake - Pınarbaşı, Aysun (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2019)
The main topic of this thesis is the transportation of injured persons to the hospitals after a large-scale disaster. The main tool for solving the problem is machine scheduling. Machine scheduling in production planning activities of enterprises is a frequent activity in short-term planning and it is very important to use resources efficiently. The scheduling of identical parallel machines is adapted to the humanitarian logistics problem. List scheduling method is applied for makespan minimization. The results show comparisons of the shortest processing time (SPT) and longest processing time (LPT) rules to get the optimum sequence for the addressed problem by an algorithm. For the heuristic method; single vehicle, 2 vehicles and 3 vehicles cases are discussed. First of all, both demographic and geographic information have provided about Istanbul. It is assumed that in a case of a large-scale earthquake in İstanbul, the city is divided into regions by Voronoi diagram. The strategy is to dispatch him/her to the closest hospital according to location of the victim. The objective function of the study is to maximize the number of seriously injured people in post-disaster period by a proper assignment of existing ambulances to patients and the expected value of service level at the same time. The service level increases as the expected travel distance of patients decreases having inverse relation. Keywords: Humanitarian logistics, Earthquake, Disaster management, List scheduling, Heuristic method.

ÖZ: Bu tezin ana konusu, ağır yaralı kişilerin büyük çaplı bir felaketten sonra hastanelere ulaştırılmasıdır. Problemi çözmek için makine çizelgeleme yöntemi kullanılmıştır. İşletmelerde üretim planlama faaliyetleri için kullanılan makine çizelgeleme, kısa süreli planlamada sık uygulanmaktadır ve kaynakların verimli kullanımında büyük önem taşımaktadır. Özdeş makine çizelgeleme insani lojistik problemlerine uyarlanmıştır. Uygulanan Liste Çizelgeleme yöntemi yaralıların hastaneye taşınması için geçen toplam süreyi en aza indirmeyi amaçlamaktadır. Çalışmada, elde edilen sonuçlar, geliştirilen algoritma ile ele alınan problem için en uygun işlem sırasını elde etmede en kısa işlem süresi (SPT) ve en uzun işlem süresi (LPT) kurallarının karşılaştırmasını göstermektedir. Sezgisel yöntem için; tek araç, 2 araç ve 3 araç durumları incelenmiştir. Öncelikle, İstanbul hakkında hem demografik hem de coğrafi bilgiler sağlanmıştır. İstanbul'da büyük çaplı bir deprem olması durumunda, kentin Voronoi diyagramı ile bölgelere ayrıldığı varsayılmaktadır. Strateji, depremzedenin bulunduğu yere göre onu en yakın hastaneye taşımaktır. Çalışmanın amaç fonksiyonu, afet sonrası dönemde mevcut ambulansların hastalara uygun şekilde atanması ile kurtarılan ağır yaralıların sayısını ve aynı zamanda beklenen hizmet seviyesini maksimize etmektir. Anahtar kelimeler: İnsani lojistik, Deprem, Afet yönetimi, Liste çizelgeleme, Sezgisel yöntem
Master of Science in Industrial Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Industrial Engineering, 2019. Supervisor: Prof. Dr. Bela Vizvari.
Keywords: Industrial Engineering; Emergency Services--Management--Planning; Humanitarian logistics; Earthquake; Disaster management; List scheduling; Heuristic method